A corpus analysis on the semantics of Semai idiomatic expressions / Sharina Saad...[et al.] - Saad, Sharina; Abdul Aziz, Nurazila; Abdul Rahman, Azlan; Mansor, Nur Syazwanie; Bidin, Samsiah (Universiti Teknologi MARA, Kedah, 2013)
Indigenous community in Malaysia is divided into three main groups which are Proto Malay, Senoi and Negrito. Semai community is a sub-group of Senoi which is the biggest group in Malaysia. (Nicholas, 2000, p.4). As the largest indigenous community in Malaysia, Semai has mostly 42383 speakers, representing several distinct dialects. Semai language is not a written language and most Semai speak the Aslian language, related to the Austro- Asiatic and the Mon-Khmer language family of mainland Southeast Asia. As it is not a written language, of late, there is a fear that the language may face gradual erosion and finally extinction as not all Semai people speak Semai language. The rapid growth of economic, education and urbanization, have affected the Semai lifestyles and attitudes on the many aspects of life including their native language. At school, the Semai younger generations learn majority languages such as Bahasa Malaysia and English and Semai language is not the main language learnt. Some of the Semai younger generation, feel inferior to speak their mother-tongue. Furthermore, the culture or life of a tribe is very much influenced by the language they use.